Views and experience of breastfeeding in public: A qualitative systematic review. Issue 4 (1st August 2022) - Grant, Aimee; Pell, Bethan; Copeland, Lauren; Brown, Amy; Ellis, Rebecca; Morris, Delyth; Williams, Denitza; Phillips, Rhiannon
Abstract: Breastfeeding rates in many Global North countries are low. Qualitative research highlights that breastfeeding in public is a particular challenge, despite mothers often having the legal right to do so. To identify barriers and facilitators, we systematically searched the qualitative research from Organisation for Economic Co‐operation and Development countries relating to breastfeeding in public spaces from 2007 to 2021. Data were analysed using the Thematic Synthesis technique. The review was registered with PROSPERO (registration number: CRD42017081504). Database searching identified 3570 unique records. In total, 74 papers, theses, or book chapters, relating to 71 studies, were included, accounting for over 17, 000 mothers. Overall, data quality was high. Our analysis identified that five core factors influenced mothers' thought processes and their breastfeeding in public behaviour: legal system; structural (in)equality; knowledge; beliefs and the social environment . Macro‐level factors relating to legislation and inequality urgently require redress if breastfeeding rates are to be increased. Widespread culture change is also required to enhance knowledge, change hostile beliefs and thus the social environment in which mother/infant dyads exist. In particular, the sexualisation of breasts, disgust narratives and lack of exposure among observers to baby‐led infant feeding patterns resulted in beliefs which created a stigmatising environment. In this context, many mothers felt unable to breastfeed in public; those who breastfed outside the home were usually highly self‐aware, attempting to reduce their exposure to conflict. Evidence‐based theoretically informed interventions to remove barriers to breastfeeding in public are urgently required. Abstract : Factors influencing mothers' infant feeding in public spaces Key messages: In OECD countries, there was limited evidence that women routinely breastfed outside of the home; for those who did, this experience was often uncomfortable. Legal protections for breastfeeding in public, where present, were not widely known and appeared to be under‐enforced. Mothers were aware of stigma relating to breastfeeding in public and feared conflict with strangers. This fear was not felt evenly, with mothers who were young, poor, and from marginalised ethnicities reporting increased surveillance and stigma. There is limited and dichotomous evidence relating to partners, family, and friends' roles in supporting mothers to breastfeed in public. Observers of breastfeeding in public had poor understanding of normal infant feeding behaviour and the associated need to breastfeed in public spaces. They also experienced disgusted reactions to viewing breastfeeding.